(untitled) (ETIKONOMI, 2018)
Financial literacy is one of the relevant facts in improving the economy. The purpose of this study was to examine the influence of demographic factors (i.e., marital status, education level, income, and age) and financial socialization agent on financial literacy. Using online and offline questionnaire survey from 100 respondents in Surabaya, East Java, and the study revealed that education level, personal income, and financial socialization agent, give the positive effect, while the marital status and age does not affect financial literacy. This result implies that the government can focus on educating the development and improvement of financial literacy for the society. It is believed to be a step forward in practicing financial planning from an early age to solve problems with financial management using financial knowledge, financial attitude, and financial behavior. DOI: 10.15408/etk.v17i2.6681